The Effect of Stream-Based Teaching Materials Using Android on Students’ Problem-Solving Skills and Religious Attitudes - Leny Heliawati; Didit Ardianto; Fenny Pebriani (AT-TA'LIM, 2022)
This study aims to develop water teaching materials using android on students’ problem-solving skills and religious attitudes with a learning model of the Science, Technology, Religious, Engineering, Art, and Mathematics (STREAM) approach science subjects. The experimental method carried out by R and D uses the 4D design (Define, Design, Develop and Disseminate). The research data were collected and analyzed in the form of quantitative descriptive from the results of the students’ pretest and posttest. This research was conducted through a google form by distributing a questionnaire, which was given to students with 50 respondents and five science teachers who had used STREAM-based water teaching materials using android. The results of the study, the average percentage of problem-solving skills with N Gain was 73% with a high category, which means that the application of learning materials based on android is proven to improve student learning. Assessment of religious attitudes in integrating material with the verses of the Quran is very good. This study’s conclusion shows that learning using STREAM-based teaching materials using android is statistically very significant, proven to be effective in improving students’ problem-solving skills and religious attitudes to water material in online learning during the current pandemic.